2018
DOI: 10.1007/s10198-018-1018-7
|View full text |Cite
|
Sign up to set email alerts
|

Unemployment and suicide in Italy: evidence of a long-run association mitigated by public unemployment spending

Abstract: From the mid-1990s on, the suicide rate in Italy declined steadily, then apparently rising again after the onset of the Great Recession, along with a sharp increase in unemployment. The aim of this study is to test the association between the suicide rate and unemployment (i.e., the unemployment rate for males and females in the period 1977-2015 and the long-term unemployment rate in the period 1983-2012) in Italy, by means of co-integration techniques. The analysis was adjusted for public unemployment spendin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 42 publications
(42 reference statements)
0
20
0
Order By: Relevance
“…North America and Asia. [5][6][7][8][9][10] Indeed, in Japan, following the collapse of the asset bubble in 1991 and the Asian economic crisis in 1997, both the unemployment rate and suicide mortality drastically increased in Japan (online supplementary appendix 1). 11 12 This Japanese public health crisis started to improve in 2009.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…North America and Asia. [5][6][7][8][9][10] Indeed, in Japan, following the collapse of the asset bubble in 1991 and the Asian economic crisis in 1997, both the unemployment rate and suicide mortality drastically increased in Japan (online supplementary appendix 1). 11 12 This Japanese public health crisis started to improve in 2009.…”
Section: Open Accessmentioning
confidence: 99%
“…In this study, we hypothesised that suicide mortality has gender-specific and age-specific sensitivities to unemployment rate, GDP per capita and EFECBSC, based on previous findings about the impacts of macroeconomic factors and governmental financial support on suicide mortality. [5][6][7][8][9][10] Therefore, to develop a more cost-effective, evidence-based regional suicide mortality prevention programme, in this study, we analyse the impacts of prefecture-disaggregated unemployment rate, GDP per capita and the regional (prefectural/municipal) implementation amount of EFECBSC to 10 sub-divisions on gender and age disaggregated suicide mortalities between 2009 and 2018 when national suicide mortality has been decreasing.…”
Section: Open Accessmentioning
confidence: 99%
“…Chang and Chen (21) and Lin and Chen (22) suggested that suicide rates are pro-cyclical corresponding to the changes in the unemployment rate in the US. Mattei and Pistoresi (10) found a continuing effect deep-rooted up to 18 years in Italy with a 1% increase in long-term unemployment add up to the suicide rate by 0.83%.…”
Section: Introductionmentioning
confidence: 96%
“…Breuer (12) and Reeves et al (13) used European Union data, Noh (14) with the OECD-countries data. To better understand this research, it is essential to highlight that some studies only examined austerity, otherwise known as the effect of economic generosity, policies on suicide (10,15,16), whereas other studies reviewed the linkage between business cycles and suicide rates (1,3,12,(17)(18)(19)(20). Another aspect that can also have an influence on suicide is economic fluctuations.…”
Section: Introductionmentioning
confidence: 99%
“…Research shows that economic recessions are harmful for mental health. Deleterious effects have been detected for self-reported symptoms of poor mental health (McInerney et al, 2013), mental health-related hospitalisations (Engelberg and Parsons, 2013), prescriptions for anti -anxiety and anti-depressant medications (Bradford and Lastrapes, 2014), searches on the Internet for 'depression' and 'anxiety' (Tefft, 2011), and suicide rates (Ruhm, 2000;Phillips and Nugent, 2014 ;Breuer, 2015;Mattei and Pistoresi, 2019). It has also been found that recessions reduce life satisfaction (Di Tella et al, 2003;Luechinger et al, 2010) .…”
Section: Introductionmentioning
confidence: 99%